Pengaruh Penambahan Batu Kapur Terhadap Kuat Geser Dan Daya Dukung Tanah Lempung - Edo Aristianto; Suradji Gandi; Okrobianus Hendri (Media Ilmiah Teknik Sipil, 2021)
Generally most of Tewang Rangkang area, Tewang Sangalang Garing District, Katingan Regency of Central Kalimantan Province is covered by clay soil with considerable development (high plasticity), the volume will change (expand) when the water content increases (changes). The volume will increase in wet conditions and will shrink when in dry conditions. It is this trait that causes damage to the construction of buildings. The purpose of this study is to know the addition of limestone to the strong value of shear and the carrying capacity of clay soil. This test was done by mixing limestone with soil in a mixture variation of 0%, 5%, 7.5%, 10%, 12.5%. Based on the results of direct shear testing against the strong value of shear and carrying capacity in the original soil obtained a strong value of shear (τ) = 0.184 kg / cm2, qult = 3.36 kg / cm2, after the addition of limestone 12.5% curing 7 days obtained strong shear value (τ) = 0.219 kg / cm2, qult = 26.04 kg / cm2, so that with the addition of limestone gives an influence on the increase in the strong value of shear and the carrying capacity of clay soil.